Endocan Measurement for Active Behçet Disease - Ayhan KUL,; Orhan ATEŞ,; Meltem ALKAN MELİKOĞLU,; Mahir UĞUR,; Nurinnisa ÖZTÜRK,; Gülsüm ERKAYHAN,; İbrahim KOÇER, (Archives of Rheumatology, 2017)
Objectives: This study aims to investigate the relationships between serum endocan, vascular endothelial growth factor (VEGF), and tumor necrosis factor-alpha (TNF-α) levels in active Behçet disease. Patients and methods: Forty patients with active Behçet disease (24 males, 16 females; mean age 37.6±8.7 years; range 20 to 50 years) and 40 healthy controls (22 males, 18 females; mean age 38.8±7.9 years; range 21 to 52 years) were included in this study. Both patient and control groups underwent a complete systemic and ophthalmic examination by the same specialist. Endocan, VEGF, and TNF-α levels were measured with an enzyme-linked immunosorbent assay kit in all subjects. Results: Serum endocan levels were 775.2±479.3 ng/mL and 275.8±145.8 ng/mL in the patient and control groups, respectively. VEGF levels were 1768.2±900.5 pg/mL and 980.2±135.3 pg/mL in the patient and control groups, respectively. TNF-α levels were 22.4±74.3 pg/mL-1 and 11.4±16.9 pg/mL-1 in the patient and control groups, respectively. There was a statistically significant difference between groups in terms of serum endocan, VEGF, and TNF-α levels. There was a significant positive correlation between serum endocan and VEGF levels in the patient group (r=0.630; p<0.001). Also, there was a significant positive correlation between serum endocan and TNF-α levels in the patient group (r=0.713; p<0.001). Conclusion: Serum endocan level may be a new marker in evaluation of both the prognosis and activity of Behçet disease.